Sex, information and condom use among peruvian adolescents - García, Patricia J.; Cotrina, Armando; Cárcamo, César; Shah, Sural (Brazilian Journal of Sexually Transmitted Diseases, 2009)
Introduction: there is an increasing concern for the STI /HIV infection risks within adolescents. Condoms are one of the most effective prevention strategies for STI/HIV, but there is no information available regarding knowledge, information and condom use among adolescents in Peru. Objective: to evaluate knowledge on STI/HIV, sources of information and sexual behaviors and analyze factors associated with sexual experience and condom use among Peruvian adolescents. Methods: we conducted a cross-sectional survey using a household-based multistage sampling in three Peruvian cities. The survey included 2,607 12-19 year-old adolescents. Results: over 80% of adolescents reported having ever heard of STIs, acknowledging teachers as their main source of information, though 40% considered school-based sexual education insufficient. 21.8% females, 41.8% males 15-19 year-old, and 1.4% females, 4.1% males 12-14 year-old reported having had sex. Only a third of adolescents reported using a condom on sexual debut. About 6.5% of males and 43% of women reported STI-related symptoms last year. Sexual experience was negatively associated with being enrolled in school for both genders (OR: 0.2 [0.1-0.3]) and positively associated with report of insufficient sexual education for males (OR: 1.7 [1.1-2.6]). School as a source of sexual knowledge was associated with condom use at last intercourse (OR: 35.7 [6.0-213.4]) for women whereas for males was knowledge of where to obtain condoms (OR: 39.6 [3.8-414.6]). For both genders, use of condom at first sexual intercourse was associated with use at recent sexual intercourse. (OR: 5.7 [1.2- 27.9]). Conclusion: results emphasize gender disparities in predictors of sexual experience and condom use in adolescents, and stress the connection between sexual education and risk behaviors. Data is valuable to guide national policies which need to address better school-based sexual education, accessibility to condoms and to adolescent reproductive health services.